EXTERNAL MALE GENITALIA OF TWO SPECIES OF GENUS PARAGUS LATREILLE (DIPTERA : SYRPHIDAE) - SINGH, AWTAR; GUPTA, VIPUL; SODHI, NAVJOT S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
A study of the external male genitalia of two species of the genus Paragus Latreille. viz. P. serratus Fabricius and P. rufiventris Brunetti has been made.